2009
DOI: 10.1007/s10562-009-9939-5
|View full text |Cite
|
Sign up to set email alerts
|

OMS-2 Catalysts for Formaldehyde Oxidation: Effects of Ce and Pt on Structure and Performance of the Catalysts

Abstract: OMS-2 (2 9 2 type octahedral molecular sieve) and cerium doped OMS-2 were synthesized by refluxing method. The platinum doped on both samples was prepared by impregnation method for catalytic oxidation of formaldehyde. These catalysts were characterized by BET, XRD, SEM, H 2 -TPR and Laser Raman. Results show that OMS-2 formed needle-shape nanocrystal structure. The addition of Ce before the formation of the OMS-2 structure obstructs the process due to mismatch of the cation size. Rather than into the framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 23 publications
6
40
1
2
Order By: Relevance
“…7) support this hypothesis: the doped samples are easier to reduce than the original material. This effect was also observed in previous studies [40,41]. In particular, Wang and Li studied the effect of platinum on the properties of cryptomelane, and found that the reducibility of this material clearly increased, due to the formation of lattice defects [41].…”
Section: Manganese Valence Oxygen Vacancies and Reducibilitysupporting
confidence: 80%
“…7) support this hypothesis: the doped samples are easier to reduce than the original material. This effect was also observed in previous studies [40,41]. In particular, Wang and Li studied the effect of platinum on the properties of cryptomelane, and found that the reducibility of this material clearly increased, due to the formation of lattice defects [41].…”
Section: Manganese Valence Oxygen Vacancies and Reducibilitysupporting
confidence: 80%
“…Great efforts have been made to reduce the indoor emission of HCHO for satisfying the stringent environmental regulations. As one of the most attractive approach, low-temperature catalytic oxidation of formaldehyde (HCHO) to CO 2 and H 2 O has received considerable attention [1][2][3][4][5][6][7][8][9][10][11][12][13]. A variety of catalysts, such as transition metal oxides [12,13], composite oxides [1], and supported noble metals have been used for this process [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, significant progresses on decreasing the reaction temperature of HCHO oxidation have been achieved over supported Pt catalysts [3][4][5][6]11]. For instance, Zhang et al [3,4] reported that a highly active Pt/TiO 2 catalyst, prepared by impregnation method, could completely oxidize HCHO even at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The feed gas was 0.15 ± 0.01 vol.% HCHO balanced with air (1500 ± 100 mL m −3 ). The high concentration of HCHO used in this study was to simulate the removal of industrial formaledehyde [24][25][26]. Gaseous HCHO was generated by flowing dry air over the paraformaldehyde heated at 50 • C. The total flow rate was 100 mL min −1 .…”
Section: Formaldehyde Oxidation Catalyzed By Spinel Ferritesmentioning
confidence: 99%